2023
DOI: 10.3390/nu15082013
|View full text |Cite
|
Sign up to set email alerts
|

Processing and Nutritional Quality of Breakfast Cereals Sold in Italy: Results from the Food Labelling of Italian Products (FLIP) Study

Abstract: This study aimed to compare the level of processing (as assessed by the NOVA classification) and the nutritional quality (as assessed by nutrition values, Nutri-Score and NutrInform battery) of breakfast cereals currently on the Italian market. A total of 349 items were found, mostly belonging to the NOVA 4 group (66.5%) and to Nutri-Score C and A (40% and 30%, respectively). The NOVA 4 products showed the highest energy, total fat, saturates, and sugar content per 100 g and had the highest number of items wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…This finding is in line with studies from other countries using different nutrient indices ( 23 , 28 ) . For example, comparing breakfast cereals across NOVA groups indicated that minimally processed foods were not always healthier based on their nutritional profile, with some ultra-processed foods also scoring well on NutriScore and differences being dependent on the serving size used for comparison ( 41 ) . Given the adverse impacts of high intakes of nutritionally poor foods high in fat, sugar and salt ( 42 44 ) , transnational corporations have reformulated their products to contain less fat, saturated fat, added sugar or salt ( 45 ) .…”
Section: Discussionmentioning
confidence: 99%
“…This finding is in line with studies from other countries using different nutrient indices ( 23 , 28 ) . For example, comparing breakfast cereals across NOVA groups indicated that minimally processed foods were not always healthier based on their nutritional profile, with some ultra-processed foods also scoring well on NutriScore and differences being dependent on the serving size used for comparison ( 41 ) . Given the adverse impacts of high intakes of nutritionally poor foods high in fat, sugar and salt ( 42 44 ) , transnational corporations have reformulated their products to contain less fat, saturated fat, added sugar or salt ( 45 ) .…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly reported limitation (n = 15) was part of Other Dimensions of Food Quality, which was the lack of consideration of ultra-processed foods (UPFs). UPFs can sometimes achieve a better NS grade than less processed foods (Angelino et al, 2023;Ebner et al, 2022;Fedde et al, 2022;Hau & Lange, 2023). This was also commonly reported with reference to Food-based limitations such as oils (n = 10) (Hau & Lange, 2023;Septia Irawan et al, 2022) and cheeses (n = 9) (Ebner et al, 2022;Fialon et al, 2022), which can be less processed than UPFs but often get lower grades, which may indicate a noncompliance of NS with FBDG.…”
Section: Reported Limitations Of Ns2021 Algorithmmentioning
confidence: 62%
“…Our literature review captured 30 papers: 24 original research (Angelino et al, 2023;Braesco et al, 2022;Bryngelsson et al, 2022;Cutroneo et al, 2022;de las Heras-Delgado et al, 2023;Dickie et al, 2022;Ebner et al, 2022;Fedde et al, 2022;Ferreiro et al, 2021;Fialon et al, 2022;Hafner & Pravst, 2021, 2023Huybers & Roodenburg, 2023;Katsouri et al, 2021;Kissock et al, 2022;Konings et al, 2022;Panczyk et al, 2023;Pitt et al, 2023;Pointke & Pawelzik, 2022;Rodriguez-Martin et al, 2023;Septia Irawan et al, 2022;Stiletto & Trestini, 2022;Borg et al, 2021;Valenzuela et al, 2022), 3 communication/correspondence (Carruba et al, 2022;Drewnowski et al, 2021;Hau & Lange, 2023), and 3 review papers (Peonides et al, 2022;van der Bend et al, 2022;Włodarek & Dobrowolski, 2022), originating from 19 countries (including 12 EU member states). The list of reported limitations (n = 20), their connections, and the numbers of mentions are presented in Figure 2.…”
Section: Reported Limitations Of Ns2021 Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…The other studies published in this Special Issue focused on different aspects, such as the overlap between the NOVA classification and other systems. In this regard, Angelino and colleagues compared the level of processing (assessed by NOVA) and nutritional quality (assessed by nutritional values, the Nutri-Score and the NutrInform battery) of breakfast cereals available on the Italian market and found a partial overlap between the NOVA classification and the systems based on the nutritional quality of foods [ 17 ]. Similarly, Grech et al used data from the 2011–2012 National Nutrition and Physical Activity Survey, a large cross-sectional study representative of the Australian population, to compare the NOVA classification system with the Australian Dietary Guidelines (ADG) in classifying foods as healthy and unhealthy through their effectiveness in predicting energy overconsumption and body mass index (BMI) [ 18 ].…”
mentioning
confidence: 99%